2002
DOI: 10.1046/j.1365-2958.2002.03196.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional analysis of the type III secretion signal of the Salmonella enterica InvJ protein

Abstract: Summary Central to the pathogenicity of Salmonella enterica is the function of a type III secretion system (TTSS) encoded within a pathogenicity island at centisome 63 (SPI‐1). An essential component of this system is a supramolecular structure termed the needle complex. Proteins to be delivered into host cells possess specific signals that route them to the type III secretion pathway. In addition, some bacterial proteins have signals that deliver them to the secretion complex to either become their structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 33 publications
(51 reference statements)
8
72
1
1
Order By: Relevance
“…Similar results have also been reported for the secretion signal consisting of the first 28 codons of a plant effector protein from Xanthomonas campestris (AvrBs2) and the secretion signal consisting of codons 4 to 7 of a secretion substrate from Salmonella enterica (InvJ) (24,30). Further, synonymous substitutions of codons, which change the sequence of the mRNA but leave the amino acid sequence intact, render the minimal secretion signal of yopQ or yopN nonfunctional (27,28).…”
supporting
confidence: 80%
“…Similar results have also been reported for the secretion signal consisting of the first 28 codons of a plant effector protein from Xanthomonas campestris (AvrBs2) and the secretion signal consisting of codons 4 to 7 of a secretion substrate from Salmonella enterica (InvJ) (24,30). Further, synonymous substitutions of codons, which change the sequence of the mRNA but leave the amino acid sequence intact, render the minimal secretion signal of yopQ or yopN nonfunctional (27,28).…”
supporting
confidence: 80%
“…In fact, the length of the needles obtained from these mutants resembled the length of those observed in needle complexes obtained from the ΔinvJ mutant strain (16). It has been previously shown that secretion of InvJ through the TTSS is required for this regulatory protein to exert its function in needle complex assembly and substrate switching (26). To ascertain whether InvJ secretion was affected in the PrgJ mutants we examined the culture supernatants of these mutants for the presence of InvJ.…”
Section: Resultsmentioning
confidence: 78%
“…The yscP-null mutant shows a leaky phenotype with regards to Yop secretion, since the mutant is still cytotoxic for HeLa cells. This is in contrast to fliK flagellar mutants and invJ mutants of Salmonella, which are impaired in substrate secretion (41,51). The reason behind this difference Mutations in the cytoplasmic region of YscU were introduced in trans into the yscP yscU-double-null strain.…”
Section: Discussionmentioning
confidence: 99%